Exploring digital fiction as a tool for teenage body image bibliotherapy*. Issue 3 (2nd July 2016) - Ensslin, Astrid; Skains, Lyle; Riley, Sarah; Haran, Joan; Mackiewicz, Alison; Halliwell, Emma
ABSTRACT: This article reflects on the findings of the interdisciplinary 'TransForm' project, which ran between 2012 and 2014 and aimed to explore how reading and writing digital fictions (DFs) might support young women in developing frameworks for more positive thinking regarding their body image. The project comprised the following stages: (1) a review and compilation of DFs thematising and/or problematising female corporeality; (2) a series of cooperative inquiries with 3 groups of young women (aged 16–19 years) over a period of 5 weeks, examining participants' responses to a selection of the previously compiled DFs, as well as the challenges these young women face in relation to body image and (3) an interventionist summer school in which participants aged 16–19 explored body image issues via writing DFs. This article reports on the main observations and findings of each stage, and draws conclusions for future research needs in this area.